2022
DOI: 10.1007/s41465-022-00244-9
|View full text |Cite
|
Sign up to set email alerts
|

Super-Men and Wonder-Women: the Relationship Between the Acceptance of Self-enhancement, Personality, and Values

Abstract: Due to ongoing technological innovations, self-enhancement methods are publicly discussed, researched from different perspectives, and part of ethical debates. However, only few studies investigated the acceptance of these methods and its relationship with personality traits and values. The present study investigated to what extent people accept different enhancement methods and whether acceptance can be predicted by Big Five and Dark Triad traits, vulnerable narcissism, and values. In an online survey (N = 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 90 publications
6
17
0
Order By: Relevance
“…This finding is reasonable given the aforementioned nomenclature (e.g., creativity, culture, fantasy, intellect), facets (aesthetic, emotional, intellectual and practical aptitude) and definition of openness in terms of appreciation of and interest in art and beauty, unusual ideas and values, new and diverse experiences, and intellectual curiosity ( 16 , 19 ). Additionally, our finding that lower agreeableness predicted higher willingness towards performance enhancement and body modification is consistent with recent evidence from an Austrian survey indicating that agreeableness correlates negatively with acceptance of human enhancement ( 23 ). It also mirrors findings from a comparison of body-modified (tattoos and piercings) and non-modified persons ( 34 , 37 ) and body piercing contemplators ( 40 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is reasonable given the aforementioned nomenclature (e.g., creativity, culture, fantasy, intellect), facets (aesthetic, emotional, intellectual and practical aptitude) and definition of openness in terms of appreciation of and interest in art and beauty, unusual ideas and values, new and diverse experiences, and intellectual curiosity ( 16 , 19 ). Additionally, our finding that lower agreeableness predicted higher willingness towards performance enhancement and body modification is consistent with recent evidence from an Austrian survey indicating that agreeableness correlates negatively with acceptance of human enhancement ( 23 ). It also mirrors findings from a comparison of body-modified (tattoos and piercings) and non-modified persons ( 34 , 37 ) and body piercing contemplators ( 40 ).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, it was found that attitudes towards human enhancement and body modification seems to differ by type with more negative attitudes towards pharmacological and genetic enhancement than current-based enhancement and mind uploading ( 22 ). In a similar study ( 23 ), agreeableness and conscientiousness correlated negatively with acceptance of human enhancement and body modification. Agreeableness and conscientiousness in particular correlated negatively with acceptance of genetic enhancement with conscientiousness having an additional negative correlation with deep brain stimulation.…”
Section: Introductionmentioning
confidence: 74%
“…Shared motifs seem to be associated with evaluating the species (vaccination) and its genus (Human Enhancement), which do not require explicit linkage and academic classi cation. This is consistent with the observation that one general factor can explain over half of the variance in the personal willingness to use various and differing Human Enhancement associated means [27]. Perceived naturalness and perceived invasiveness seem to be good starting points for further evaluation of the characteristics of such factor.…”
Section: Discussionsupporting
confidence: 88%
“…Measuring the willingness to use an enhancement is common when assessing attitudes toward Human Enhancement and was employed in various other studies [cf. 27,40,[50][51][52]. Models employed willingness to use as outcome and, among others, perceived naturalness and perceived invasiveness as predictors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation